The Jumper - Parrish, Tim (Texas Review Press, 2013)
"Set amidst North Baton Rouge's inferno of industries and refineries, smack in the middle of low-rent crime and violence, The jumper is a fast-paced and gritty tale about characters who'd intimidate the thugs of a 1930s hard-boiled novel. Parrish's visceral yet lyrical prose, his structuring of fictional time, and his clear moral vision transform these tough-guy elements into an experience somehow luminescent, emotionally disturbing, and completely uplifting."--Back cover.
Keywords: Fiction; Young men; dept.eng; faculty_collection